Preparation method, product and application of modified chitosan scale inhibitor
Through the preparation of modified chitosan scale inhibitors, the lattice distortion and chelation solubilization mechanisms are used to solve the problem of metal scale blockage in high-salt wastewater, and the efficient scale inhibition and dispersion effect is achieved. It is suitable for high-salt content. Wastewater treatment.
Patent Information
- Application Number
- CN202310055709.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-16
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2043-01-16
AI Technical Summary
Existing scale inhibitors have poor effects when treating high-salt-containing wastewater, making it difficult to effectively prevent the formation and removal of metal scale, resulting in blockage of pipelines and poor circulation.
Using the preparation method of modified chitosan scale inhibitor, the modified chitosan with enhanced scale inhibition properties is formed by mixing, heating and adjusting the pH of carboxymethyl chitosan and modified copolymer in a sulfuric acid solution. , lattice distortion and chelation solubilization mechanisms are used to improve the adsorption and dissolution of calcium and magnesium ions.
In high-salt wastewater, modified chitosan scale inhibitors show efficient scale inhibition dispersion effect, and the scale inhibition rate on calcium ions and magnesium ions can reach more than 95%, which is low in cost and simple in preparation, making it easy to promote.
Abstract
Description
Technical Field
[0001] The invention relates to the field of scale inhibitor preparation, and in particular to a preparation method, product and application of a modified chitosan scale inhibitor. Background Art
[0002] High-salinity wastewater is produced in the production process of oil field water pipelines, circulating cooling water pipelines and flash desalination. Because it contains a large amount of inorganic salts, a large amount of dense metal scale is attached to the pipeline or other circulation parts, which is difficult to clean, causing pipeline bulging, deformation, and even bursting, hindering the normal water circulation, causing local blockage or poor circulation. Scale inhibitor is a commonly used water treatment agent, but the common scale inhibitors currently have a certain scale inhibition and dispersion effect on low-salinity wastewater, but when facing high-salinity wastewater, the scale inhibition effect is poor, which brings certain troubles to water treatment.
[0003] For the treatment of high-salt water, it is of great significance to provide a scale inhibitor with high-efficiency scale inhibition and dispersion performance. Summary of the invention
[0004] The purpose of the present invention is to provide a preparation method, product and application of a modified chitosan scale inhibitor in view of the problems existing in the prior art.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is:
[0006] A method for preparing a modified chitosan scale inhibitor comprises the following steps:
[0007] Step 1, mixing carboxymethyl chitosan and modified copolymer in a sealed container, then adding a first sulfuric acid solution, stirring, to obtain a first material;
[0008] Step 2, then introducing an inert gas into the first material, and heating the first material to above 100° C. under stirring conditions, then stirring at a constant temperature for a period of time, and then naturally cooling to room temperature to obtain a second material;
[0009] Step 3: Under stirring conditions, adjusting the pH of the second material to neutral, standing the material to precipitate a precipitate, obtaining the precipitate, and sequentially washing, drying and grinding the precipitate to obtain a modified chitosan scale inhibitor; wherein the modified copolymer is mainly prepared from the following raw materials by weight:
[0010] 10 to 20 parts of hydrolyzed polymaleic anhydride; 5 to 10 parts of lauryl alcohol acrylate; 15 to 25 parts of acrylic acid-methyl acrylate-hydroxypropyl acrylate copolymer; 6 to 11 parts of the second sulfuric acid solution;
[0011] In the step 1, the mass ratio of carboxymethyl chitosan, the modified copolymer and the first sulfuric acid solution is (200-500): (30-70): (30-60).
[0012] The present application discloses a method for preparing a modified chitosan scale inhibitor, including step 1, mixing carboxymethyl chitosan and a modified copolymer and placing them in a closed container, then adding a first sulfuric acid solution and stirring to obtain a first material; step 2, then introducing an inert gas into the first material, and heating the first material to above 100°C under stirring conditions, then naturally cooling to room temperature after constant temperature stirring for a period of time to obtain a second material; step 3, under stirring conditions, adjusting the pH of the second material to neutral to obtain a precipitate, and washing, drying and grinding the precipitate with methanol in turn to obtain a modified chitosan scale inhibitor. The preparation method uses carboxymethyl chitosan, a modified copolymer and a sulfuric acid solution as the main raw materials, and controls the mass ratio of the three raw materials. Under the control of the process parameters during the preparation process, the prepared scale inhibitor exhibits excellent scale inhibition and dispersion effects when treating high-salt wastewater, which is convenient for promotion.
[0013] Natural polymer materials, such as chitosan, cellulose, starch, etc., have attracted widespread attention in recent years due to their important advantages such as environmental friendliness, wide sources, low prices and biodegradability. Carboxymethyl chitosan is a water-soluble chitosan derivative and an amphoteric polyelectrolyte. 2 After carboxymethylation, chitosan has improved water solubility and is used as a heavy metal chelating agent.
[0014] Carboxymethyl chitosan can form a stable adsorption complex with metal ions in water and has good scale inhibition performance. Carboxymethyl chitosan has more carboxymethyl and amino functional groups. After appropriate physical and chemical modification, molecular structure grafting can be achieved, further improving the scale inhibition performance. It can be used as an efficient scale inhibitor in high-salt water scale inhibition and other fields.
[0015] Carboxymethyl chitosan achieves scale inhibition effect through lattice distortion and chelation solubilization. However, its molecular chain length is limited and the number of chelated atoms is limited, especially in high-concentration salt environment, its scale inhibition performance is difficult to meet the requirements. If the amount of carboxymethyl chitosan added is increased, it is easy to cause oversaturation, and the carboxymethyl chitosan dissolved in water and exerting scale inhibition effect is still limited. Through the grafting modification of carboxymethyl chitosan, its molecular chain is lengthened and the number of chelated atoms is increased, thereby improving its scale inhibition performance in high-concentration salt environment.
[0016] After the hydrolyzed polymaleic anhydride and acrylic acid-methyl acrylate-hydroxypropyl acrylate copolymer are mixed, sulfuric acid is added. Under the action of sulfuric acid, the hydrolyzed polymaleic anhydride and the acrylic acid-methyl acrylate-hydroxypropyl acrylate copolymer are hydrolyzed to generate organic acid. The pH is then adjusted to 5-6, and excess sulfuric acid is removed. Lauryl alcohol acrylate is added, and the lauryl alcohol acrylate with double bond functional groups undergoes esterification reaction with the organic acid to obtain the modified copolymer.
[0017] The reasons for the enhanced anti-scaling effect are:
[0018] (1) Lattice distortion
[0019] When the crystals of slightly soluble substances such as calcium salts and magnesium salts are generated, they are arranged according to a certain lattice, and the crystals are dense and hard, thus forming scale. Modified chitosan scale inhibitors are adsorbed on the crystals and doped in the lattice lattice, interfering with the crystallization of inorganic scale. Compared with unmodified chitosan, the molecular branches of the grafted modified polysaccharide scale inhibitors grow, which causes the scale inhibitor to enter the crystal deeper and at more complex and diverse angles, thereby forming a stronger interference and destruction to the formation of inorganic scale crystals. In addition, part of the scale inhibitor adsorbed on the lattice is drawn into the lattice as the crystal grows, causing the originally regular lattice to be dislocated, forming holes in the scale layer, and reducing the interaction between the lattice units, thereby loosening the metal scale and making it easy to remove and disperse.
[0020] (2) Chelation and solubilization
[0021] Scale inhibitors can form soluble chelates with calcium and magnesium ions in water, allowing more metal ions to dissolve in water, which is equivalent to increasing the solubility of calcium and magnesium salts, thereby reducing the possibility of metal scale formation. The modified grafted chitosan scale inhibitor has an increased number of chelated atoms, which enhances the chelation effect, increases the stability of the soluble metal chelate, and improves the solubility of metal ions.
[0022] Further, in step 1, the mass ratio of carboxymethyl chitosan to the modified copolymer is 4 to 12:1. Studies have found that controlling the mass ratio of carboxymethyl chitosan to the modified copolymer within an appropriate range can better ensure the excellent scale inhibition and dispersion effect of the scale inhibitor. Preferably, in step 1, the mass ratio of carboxymethyl chitosan to the modified copolymer is 5 to 12:1. More preferably, in step 1, the mass ratio of carboxymethyl chitosan to the modified copolymer is 5 to 10:1.
[0023] Furthermore, the mass fraction of the first sulfuric acid solution in step 1 is 15% to 30%.
[0024] Further, the weight ratio of the total amount of the hydrolyzed polymaleic anhydride and the acrylic acid-methyl acrylate-hydroxypropyl acrylate copolymer to the lauryl alcohol acrylate is 0.8 to 2:1. After extensive research by the inventors, it was found that the weight ratio of the total amount of the hydrolyzed polymaleic anhydride and the acrylic acid-methyl acrylate-hydroxypropyl acrylate copolymer to the lauryl alcohol acrylate is an important factor affecting the final scale inhibition effect of the scale inhibitor product. If the weight ratio is too low or too small, the scale inhibition effect of the scale inhibitor on calcium ions and magnesium ions will be significantly reduced. Preferably, the weight ratio of the total amount of the hydrolyzed polymaleic anhydride and the acrylic acid-methyl acrylate-hydroxypropyl acrylate copolymer to the lauryl alcohol acrylate is 1 to 2:1. More preferably, the weight ratio of the total amount of the hydrolyzed polymaleic anhydride and the acrylic acid-methyl acrylate-hydroxypropyl acrylate copolymer to the lauryl alcohol acrylate is 1 to 1.8:1.
[0025] Furthermore, the modified copolymer is mainly prepared by the following method: first, the hydrolyzed polymaleic anhydride and the acrylic acid-methyl acrylate-hydroxypropyl acrylate copolymer are mixed, a second sulfuric acid solution is added, and stirred for more than 2 hours, then the pH is adjusted to 5-6, and the lauryl alcohol acrylate is added, and stirring is continued for more than 2 hours to obtain a modified copolymer.
[0026] Furthermore, the mass fraction of the second sulfuric acid solution is 30% to 60%.
[0027] Furthermore, during the preparation of the modified copolymer, the stirring temperature is 60° C. to 80° C., and the stirring rate is 50 r / min to 80 r / min.
[0028] Furthermore, during the preparation of the modified copolymer, the stirring time is 3 h to 8 h. Preferably, during the preparation of the modified copolymer, the stirring time is 3 h to 7 h.
[0029] Furthermore, in step 2, the first material is heated to 100°C to 120°C and stirred at a constant temperature for more than 6 hours. Studies have found that the heating temperature of the first material and the constant temperature stirring time are important factors affecting the scale inhibition and dispersion effect of the scale inhibitor product. Preferably, in step 2, the first material is heated to 100°C to 118°C and stirred at a constant temperature for 6 hours to 8 hours. More preferably, in step 2, the first material is heated to 100°C to 115°C and stirred at a constant temperature for 7 hours to 8 hours.
[0030] Further, in step 2, the stirring rate is 90 r / min to 120 r / min. Preferably, in step 2, the stirring rate is 95 r / min to 120 r / min. More preferably, in step 2, the stirring rate is 100 r / min to 120 r / min.
[0031] Further, in step 3, the stirring rate is 20 r / min to 50 r / min. Preferably, in step 3, the stirring rate is 25 r / min to 50 r / min. More preferably, in step 3, the stirring rate is 30 r / min to 50 r / min.
[0032] Furthermore, the carboxymethyl chitosan is mainly prepared from the following raw materials by weight: 50 to 100 parts of alkalized chitosan; 10 to 30 parts of isopropanol; and 20 to 60 parts of chloroacetic acid.
[0033] Preferably, the carboxymethyl sugar polyshell is mainly prepared from the following raw materials by weight: 60 to 100 parts of alkalized chitosan; 12 to 30 parts of isopropanol; 30 to 60 parts of chloroacetic acid. More preferably, the carboxymethyl sugar polyshell is mainly prepared from the following raw materials by weight: 60 to 90 parts of alkalized chitosan; 15 to 28 parts of isopropanol; 40 to 55 parts of chloroacetic acid. Further, the carboxymethyl chitosan is mainly prepared by the following method: the alkalized chitosan, the isopropanol and the chloroacetic acid are mixed, stirred for more than 3 hours, and then the pH is adjusted to neutral, washed, and the carboxymethyl chitosan is obtained.
[0034] Furthermore, during the preparation of carboxymethyl chitosan, the stirring temperature is 30° C. to 50° C., and the stirring rate is 100 r / min to 120 r / min.
[0035] Furthermore, during the preparation of carboxymethyl chitosan, the stirring time is 3 h to 6 h. Preferably, the stirring time is 3 h to 5 h.
[0036] Furthermore, the alkalized chitosan is mainly prepared by the following method: adding chitosan into a sodium hydroxide solution, stirring and alkalizing, and obtaining the alkalized chitosan.
[0037] Further, the average molecular weight of the chitosan is 1 million to 1.5 million, preferably, the average molecular weight of the chitosan is 1 million to 1.45 million. For example, the average molecular weight of the chitosan is 1 million, 1.1 million, 1.2 million, 1.3 million, 1.4 million, or 1.45 million, 1.5 million.
[0038] Further, the mass fraction of the sodium hydroxide solution is 15% to 30%. Preferably, the mass fraction of the sodium hydroxide solution is 20% to 25%.
[0039] Furthermore, during the preparation of alkalized chitosan, the stirring time is 3 h to 6 h. Preferably, the stirring time is 3 h to 5 h.
[0040] Furthermore, during the preparation of alkalized chitosan, the temperature during stirring is 30° C. to 50° C., and the stirring rate is 100 r / min to 120 r / min.
[0041] Another object of the present invention is to provide a product prepared by the above preparation method.
[0042] The scale inhibitor product is prepared by the preparation method of the modified chitosan scale inhibitor as described above.
[0043] Another object of the present invention is to provide an application of the product prepared by the above preparation method.
[0044] An application of the scale inhibitor product prepared by the above-mentioned preparation method of the modified chitosan scale inhibitor in the treatment of high-salt wastewater.
[0045] Furthermore, the mass fraction of calcium and / or magnesium in the high-salinity wastewater is above 5%.
[0046] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:
[0047] 1. The present application discloses a method for preparing a modified chitosan scale inhibitor, comprising step 1, mixing carboxymethyl chitosan and a modified copolymer and placing them in a closed container, then adding a first sulfuric acid solution and stirring to obtain a first material; step 2, then introducing an inert gas into the first material, and heating the first material to above 100°C under stirring conditions, then stirring at a constant temperature for a period of time, and naturally cooling to room temperature to obtain a second material; step 3, under stirring conditions, adjusting the pH of the second material to neutral to obtain a precipitate, and washing, drying and grinding the precipitate in sequence to obtain a modified chitosan scale inhibitor; the preparation method uses carboxymethyl chitosan, a modified copolymer and a sulfuric acid solution as main raw materials, and controls the mass ratio of the three raw materials. Under the control of process parameters during the preparation process, the prepared scale inhibitor exhibits excellent anti-scaling and dispersing effects when treating high-salt wastewater, and is easy to promote.
[0048] 2. The present invention provides a modified chitosan scale inhibitor product. In high-salt wastewater, when the modified chitosan scale inhibitor is added in an amount of 15 mg / L, the scale inhibition rate for calcium ions can reach more than 95%, and the scale inhibition rate for magnesium ions can reach more than 96%. It exhibits a high scale inhibition and dispersion effect on calcium ions and magnesium ions, has low cost, and a simple preparation method.
[0049] 3. The present invention provides the application of modified chitosan scale inhibitor product in the treatment of high-salt wastewater. DETAILED DESCRIPTION
[0050] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0051] In the following examples and comparative examples, hydrolyzed polymaleic anhydride (purchased from Sinopharm Chemical Reagent Co., Ltd.); lauryl alcohol acrylate (purchased from Sinopharm Chemical Reagent Co., Ltd.); acrylic acid-methyl acrylate-hydroxypropyl acrylate copolymer (powder, purchased from Sinopharm Chemical Reagent Co., Ltd.).
[0052] Example 1
[0053] Preparation of alkalized chitosan
[0054] Chitosan with an average molecular weight of 1.2 million was added to a sodium hydroxide solution with a mass fraction of 20%, and stirred for 4 hours for alkalization. The temperature during the stirring process was 40° C. and the stirring rate was 110 r / min, thereby obtaining alkalized chitosan.
[0055] Preparation of carboxymethyl chitosan
[0056] 80 parts of alkalized chitosan; 20 parts of isopropanol; 40 parts of chloroacetic acid.
[0057] The alkalized chitosan, the isopropanol and the chloroacetic acid are mixed, stirred at 40° C. for 4 hours at a stirring rate of 110 r / min, and then the pH is adjusted to be neutral, and washed to obtain carboxymethyl chitosan.
[0058] Preparation of modified copolymers
[0059] 15 parts of hydrolyzed polymaleic anhydride; 8 parts of lauryl alcohol acrylate; 20 parts of acrylic acid-methyl acrylate-hydroxypropyl acrylate copolymer; 8 parts of 40% sulfuric acid solution by mass. First, the hydrolyzed polymaleic anhydride and the acrylic acid-methyl acrylate-hydroxypropyl acrylate copolymer are mixed, and the second sulfuric acid solution is added, and stirred for more than 2 hours, and then the pH is adjusted to 5-6, and the lauryl alcohol acrylate is added, and stirring is continued for more than 2 hours to obtain a modified copolymer.
[0060] Preparation of modified chitosan scale inhibitor
[0061] Raw materials: 300 parts of carboxymethyl chitosan, 50 parts of modified copolymer, and 40 parts of 20% sulfuric acid solution by mass.
[0062] Step 1, mixing carboxymethyl chitosan and modified copolymer in a sealed container, then adding 20% by mass sulfuric acid solution, stirring, to obtain a first material;
[0063] Step 2: Then, an inert gas is introduced into the first material, and the first material is heated to 110° C. under stirring conditions, and then stirred at a constant temperature for 7 hours, and then naturally cooled to room temperature to obtain a second material; the stirring rate is 110 r / min.
[0064] Step 3: Under stirring condition of 30 r / min, sodium carbonate solution is added dropwise to the second material, the pH is adjusted to neutral, the precipitate is allowed to stand, and the precipitate is filtered, washed, dried and ground in sequence to obtain a modified chitosan scale inhibitor.
[0065] test
[0066] Take a wastewater sample with high salt and organic content produced by a printing and dyeing factory, in which the mass percentage of calcium ions is 5%, and the mass percentage of magnesium ions is 5%.
[0067] Add the modified chitosan scale inhibitor prepared in Example 1 and shake well, wherein the amount of the modified chitosan scale inhibitor is 15 mg / L, put it into a constant temperature water bath for 8 hours at a temperature of 70°C, take it out, cool it, filter it, and determine the Ca in the filtrate by EDTA complexometric titration. 2+ Mg 2+ Concentration, free Ca in water 2+ Mg 2+ Evaluate the scale inhibition effect. The scale inhibition rate calculation formula is as follows:
[0068] α=(rq) / (pq)
[0069] α——scale inhibition rate, %;
[0070] p——Concentration of metal ions in water sample before the test, mg / L;
[0071] q——Concentration of metal ions in the water sample without adding scale inhibitor after the test, mg / L;
[0072] r——Concentration of metal ions in the water sample with scale inhibitor after the test, mg / L.
[0073] It was found through testing that the modified chitosan scale inhibitor prepared in Example 1 had a scale inhibition rate of 94.5% for calcium ions and a scale inhibition rate of 96.4% for magnesium ions in the treatment of high-salt wastewater.
[0074] Example 2
[0075] Preparation of alkalized chitosan
[0076] Chitosan with an average molecular weight of 100 was added into a sodium hydroxide solution with a mass fraction of 15%, and stirred for 6 hours for alkalization. The temperature during the stirring process was 30° C. and the stirring rate was 100 r / min, so as to obtain alkalized chitosan.
[0077] Preparation of carboxymethyl chitosan
[0078] 50 parts of alkalized chitosan; 30 parts of isopropanol; 20 parts of chloroacetic acid.
[0079] The alkalized chitosan, the isopropanol and the chloroacetic acid are mixed, stirred at 50° C. for 3 hours at a stirring rate of 120 r / min, and then the pH is adjusted to be neutral, and washed to obtain carboxymethyl chitosan.
[0080] Preparation of modified copolymers
[0081] 20 parts of hydrolyzed polymaleic anhydride; 10 parts of lauryl alcohol acrylate; 25 parts of acrylic acid-methyl acrylate-hydroxypropyl acrylate copolymer; 11 parts of 30% sulfuric acid solution by mass.
[0082] First, the hydrolyzed polymaleic anhydride and the acrylic acid-methyl acrylate-hydroxypropyl acrylate copolymer are mixed, a second sulfuric acid solution is added, and the mixture is stirred for more than 2 hours. Then the pH is adjusted to 5-6, and the lauryl alcohol acrylate is added, and the mixture is stirred for more than 2 hours to obtain a modified copolymer.
[0083] Preparation of modified chitosan scale inhibitor
[0084] Raw materials: 500 parts of carboxymethyl chitosan, 70 parts of modified copolymer, and 60 parts of 20% sulfuric acid solution by mass.
[0085] Step 1, mixing carboxymethyl chitosan and modified copolymer in a sealed container, then adding 15% by mass sulfuric acid solution, stirring, to obtain a first material;
[0086] Step 2: Then, an inert gas is introduced into the first material, and the first material is heated to 100° C. under stirring conditions, and then stirred at a constant temperature for 6 hours, and then naturally cooled to room temperature to obtain a second material; the stirring rate is 120 r / min.
[0087] Step 3: under the stirring condition of 50 r / min, sodium carbonate solution is added dropwise to the second material, the pH is adjusted to neutral, the precipitate is allowed to stand, and the precipitate is filtered, washed, dried and ground in sequence to obtain a modified chitosan scale inhibitor.
[0088] The same wastewater as in Example 1 was used, and the modified chitosan scale inhibitor prepared in Example 2 was tested using the same scale inhibition method as in Example 1. The test found that the scale inhibition rate for calcium ions was 95.3%, and the scale inhibition rate for magnesium ions was 96.1%.
[0089] Example 3
[0090] Preparation of alkalized chitosan
[0091] Chitosan with an average molecular weight of 1.5 million was added to a sodium hydroxide solution with a mass fraction of 30%, and stirred for 3 hours for alkalization. The temperature during the stirring process was 50° C. and the stirring rate was 120 r / min, thereby obtaining alkalized chitosan.
[0092] Preparation of carboxymethyl chitosan
[0093] 100 parts of alkalized chitosan; 10 parts of isopropanol; 60 parts of chloroacetic acid.
[0094] The alkalized chitosan, the isopropanol and the chloroacetic acid are mixed, stirred at 30° C. for 5 hours at a stirring rate of 100 r / min, and then the pH is adjusted to be neutral, and washed to obtain carboxymethyl chitosan.
[0095] Preparation of modified copolymers
[0096] 10 parts of hydrolyzed polymaleic anhydride; 5 parts of lauryl alcohol acrylate; 15 parts of acrylic acid-methyl acrylate-hydroxypropyl acrylate copolymer; 6 parts of 60% sulfuric acid solution by mass.
[0097] First, the hydrolyzed polymaleic anhydride and the acrylic acid-methyl acrylate-hydroxypropyl acrylate copolymer are mixed, and a second sulfuric acid solution is added, and stirred for more than 2 hours at a stirring temperature of 60° C. and a stirring rate of 80 r / min. Then, the pH is adjusted to 5-6, and the lauryl alcohol acrylate is added, and stirring is continued for more than 2 hours to obtain a modified copolymer.
[0098] Preparation of modified chitosan scale inhibitor
[0099] Raw materials: 200 parts of carboxymethyl chitosan, 30 parts of modified copolymer, and 30 parts of 20% sulfuric acid solution by mass.
[0100] Step 1, mixing carboxymethyl chitosan and modified copolymer in a sealed container, then adding 30% by mass sulfuric acid solution, stirring, to obtain a first material;
[0101] Step 2: then introduce an inert gas into the first material, and heat the first material to 120° C. under stirring conditions, then stir at a constant temperature for 8 hours, and then naturally cool to room temperature to obtain a second material; the stirring rate is 90 r / min.
[0102] Step 3: Under stirring conditions, adjust the pH of the second material to neutral, let it stand to precipitate a precipitate, centrifuge and separate the precipitate, wash the precipitate with methanol, dry and grind it in sequence to obtain a modified chitosan scale inhibitor.
[0103] The same wastewater as in Example 1 was used, and the modified chitosan scale inhibitor prepared in Example 3 was tested using the same scale inhibition method as in Example 1. The test found that the scale inhibition rate for calcium ions was 94.1%, and the scale inhibition rate for magnesium ions was 95.8%.
[0104] Example 4
[0105] Preparation of alkalized chitosan
[0106] Chitosan with an average molecular weight of 1.3 million was added to a sodium hydroxide solution with a mass fraction of 25%, and stirred for 5 hours for alkalization. The temperature during the stirring process was 30° C. and the stirring rate was 110 r / min, thereby obtaining alkalized chitosan.
[0107] Preparation of carboxymethyl chitosan
[0108] 75 parts of alkalized chitosan; 25 parts of isopropanol; 45 parts of chloroacetic acid.
[0109] The alkalized chitosan, the isopropanol and the chloroacetic acid are mixed, stirred at 45° C. for 6 hours at a stirring rate of 105 r / min, and then the pH is adjusted to be neutral, and washed to obtain carboxymethyl chitosan.
[0110] Preparation of modified copolymers
[0111] 20 parts of hydrolyzed polymaleic anhydride; 10 parts of lauryl alcohol acrylate; 15 parts of acrylic acid-methyl acrylate-hydroxypropyl acrylate copolymer; 9 parts of 60% sulfuric acid solution by mass.
[0112] First, the hydrolyzed polymaleic anhydride and the acrylic acid-methyl acrylate-hydroxypropyl acrylate copolymer are mixed, and a second sulfuric acid solution is added, and stirred for more than 2 hours at a stirring temperature of 60° C. and a stirring rate of 80 r / min. Then, the pH is adjusted to 5-6, and the lauryl alcohol acrylate is added, and stirring is continued for more than 2 hours to obtain a modified copolymer.
[0113] Preparation of modified chitosan scale inhibitor
[0114] Raw materials: 450 parts of carboxymethyl chitosan, 40 parts of modified copolymer, and 40 parts of 20% sulfuric acid solution by mass.
[0115] Step 1, mixing carboxymethyl chitosan and modified copolymer in a sealed container, then adding 30% by mass sulfuric acid solution, stirring, to obtain a first material;
[0116] Step 2: Then, an inert gas is introduced into the first material, and the first material is heated to 105° C. under stirring conditions, and then stirred at a constant temperature for 6.5 hours, and then naturally cooled to room temperature to obtain a second material; the stirring rate is 100 r / min.
[0117] Step 3: Under stirring condition of 40 r / min, sodium carbonate solution is added dropwise to the second material, the pH is adjusted to neutral, the precipitate is allowed to stand, and the precipitate is filtered, washed, dried and ground in sequence to obtain a modified chitosan scale inhibitor.
[0118] The same wastewater as in Example 1 was selected, and the modified chitosan scale inhibitor prepared in Example 4 was tested using the same scale inhibition method as in Example 1. The test found that the scale inhibition rate for calcium ions was 93.7%, and the scale inhibition rate for magnesium ions was 95.6%.
[0119] Comparative Example 1
[0120] Comparative Example 1: The carboxymethyl chitosan prepared in Example 1 is directly used as a scale inhibitor.
[0121] The same wastewater as in Example 1 was selected, and the scale inhibition test method of Example 1 was used for the scale inhibitor prepared in Comparative Example 1. The test found that the scale inhibition rate for calcium ions was 45.3%, and the scale inhibition rate for magnesium ions was 47.2%.
[0122] Comparative Example 2
[0123] In Comparative Example 2, the modified copolymer prepared in Example 1 is directly used as a scale inhibitor.
[0124] The same wastewater as in Example 1 was selected, and the scale inhibition test method of Example 1 was used for the scale inhibitor prepared in Comparative Example 2. The test found that the scale inhibition rate for calcium ions was 44.1%, and the scale inhibition rate for magnesium ions was 45.2%.
[0125] Comparative Example 3
[0126] Comparative Example 3 used the carboxymethyl chitosan and modified copolymer prepared in Example 1, and only changed the preparation process of the scale inhibitor.
[0127] Preparation of antiscalant
[0128] Raw materials: 300 parts of carboxymethyl chitosan, 50 parts of modified copolymer, and 40 parts of 20% sulfuric acid solution by mass.
[0129] Step 1: mix carboxymethyl chitosan and modified copolymer and place them in a closed container, then add 20% sulfuric acid solution by mass, stir and obtain modified chitosan scale inhibitor.
[0130] The same wastewater as in Example 1 was selected, and the scale inhibition test method of Example 1 was adopted for the scale inhibitor prepared in Comparative Example 3. The test found that the scale inhibition rate for calcium ions was 46.2%, and the scale inhibition rate for magnesium ions was 46.8%.
[0131] Comparative Example 4
[0132] Comparative Example 4 used the carboxymethyl chitosan and modified copolymer prepared in Example 1, and only changed the temperature of the scale inhibitor preparation process.
[0133] Preparation of modified chitosan scale inhibitor
[0134] Raw materials: 300 parts of carboxymethyl chitosan, 50 parts of modified copolymer, and 40 parts of 20% sulfuric acid solution by mass.
[0135] Step 1, mixing carboxymethyl chitosan and modified copolymer in a sealed container, then adding 20% by mass sulfuric acid solution, stirring, to obtain a first material;
[0136] Step 2: Then, an inert gas is introduced into the first material, and the first material is heated to 80° C. under stirring conditions, and then stirred at a constant temperature for 7 hours, and then naturally cooled to room temperature to obtain a second material; the stirring rate is 110 r / min.
[0137] Step 3: Under stirring condition of 30 r / min, sodium carbonate solution is added dropwise to the second material, the pH is adjusted to neutral, the precipitate is allowed to stand, and the precipitate is filtered, washed, dried and ground in sequence to obtain a modified chitosan scale inhibitor.
[0138] The same wastewater as in Example 1 was selected, and the scale inhibition test method of Example 1 was used for the scale inhibitor prepared in Comparative Example 4. The test found that the scale inhibition rate for calcium ions was 72.4%, and the scale inhibition rate for magnesium ions was 74.5%.
[0139] Comparative Example 5
[0140] Comparative Example 5 uses the carboxymethyl chitosan prepared in Example 1, changes the formula of the modified copolymer, and the preparation method of the modified chitosan scale inhibitor is exactly the same as that of Example 1.
[0141] Specific comparative example 5-1
[0142] Preparation of modified copolymers
[0143] 8 parts of lauryl alcohol acrylate; 20 parts of acrylic acid-methyl acrylate-hydroxypropyl acrylate copolymer; 8 parts of 40% sulfuric acid solution by mass.
[0144] First, the lauryl alcohol acrylate and the acrylic acid-methyl acrylate-hydroxypropyl acrylate copolymer are mixed, a second sulfuric acid solution is added, and the mixture is stirred for more than 2 hours. Then, the pH is adjusted to 5-6, the lauryl alcohol acrylate is added, and the mixture is stirred for more than 2 hours to obtain a modified copolymer.
[0145] The same wastewater as in Example 1 was selected, and the scale inhibition test method of Example 1 was adopted for the scale inhibitor prepared in Comparative Example 6-1. The test found that the scale inhibition rate for calcium ions was 61.4%, and the scale inhibition rate for magnesium ions was 63.2%.
[0146] Comparative Example 5-2
[0147] Preparation of modified copolymers
[0148] 15 parts of hydrolyzed polymaleic anhydride; 20 parts of acrylic acid-methyl acrylate-hydroxypropyl acrylate copolymer; 8 parts of 40% sulfuric acid solution by mass.
[0149] First, the hydrolyzed polymaleic anhydride and the acrylic acid-methyl acrylate-hydroxypropyl acrylate copolymer are mixed, a second sulfuric acid solution is added, and the mixture is stirred for more than 2 hours. Then the pH is adjusted to 5-6, and the lauryl alcohol acrylate is added, and the mixture is stirred for more than 2 hours to obtain a modified copolymer.
[0150] The same wastewater as in Example 1 was selected, and the scale inhibition test method of Example 1 was adopted for the scale inhibitor prepared in Comparative Example 6-2. The test found that the scale inhibition rate for calcium ions was 61.7%, and the scale inhibition rate for magnesium ions was 62.8%.
[0151] Comparative Example 5-3
[0152] Preparation of modified copolymers
[0153] 15 parts of hydrolyzed polymaleic anhydride; 8 parts of lauryl alcohol acrylate; 8 parts of 40% sulfuric acid solution by mass.
[0154] First, the hydrolyzed polymaleic anhydride and the lauryl alcohol acrylate are mixed, a second sulfuric acid solution is added, and the mixture is stirred for more than 2 hours. Then, the pH is adjusted to 5-6, the lauryl alcohol acrylate is added, and the mixture is stirred for more than 2 hours to obtain a modified copolymer.
[0155] The same wastewater as in Example 1 was selected, and the scale inhibition test method of Example 1 was adopted for the scale inhibitor prepared in Comparative Example 6-3. The test found that the scale inhibition rate for calcium ions was 62.1%, and the scale inhibition rate for magnesium ions was 62.7%.
[0156] Comparative Example 5-4
[0157] Preparation of modified copolymers
[0158] 9 parts of hydrolyzed polymaleic anhydride; 5 parts of lauryl alcohol acrylate; 29 parts of acrylic acid-methyl acrylate-hydroxypropyl acrylate copolymer; 8 parts of 40% sulfuric acid solution by mass.
[0159] First, the hydrolyzed polymaleic anhydride, the lauryl alcohol acrylate and the acrylic acid-methyl acrylate-hydroxypropyl acrylate copolymer are mixed, a second sulfuric acid solution is added, and the mixture is stirred for more than 2 hours. Then, the pH is adjusted to 5-6, the lauryl alcohol acrylate is added, and the mixture is stirred for more than 2 hours to obtain a modified copolymer.
[0160] The same wastewater as in Example 1 was selected, and the scale inhibition test method of Example 1 was adopted for the scale inhibitor prepared in Comparative Example 6-4. The test found that the scale inhibition rate for calcium ions was 67.4%, and the scale inhibition rate for magnesium ions was 70.1%.
[0161] Comparative Example 5-5
[0162] Preparation of modified copolymers
[0163] 20 parts of hydrolyzed polymaleic anhydride; 10 parts of lauryl alcohol acrylate; 13 parts of acrylic acid-methyl acrylate-hydroxypropyl acrylate copolymer; 8 parts of 40% sulfuric acid solution by mass.
[0164] First, the hydrolyzed polymaleic anhydride, the lauryl alcohol acrylate and the acrylic acid-methyl acrylate-hydroxypropyl acrylate copolymer are mixed, a second sulfuric acid solution is added, and the mixture is stirred for more than 2 hours. Then, the pH is adjusted to 5-6, the lauryl alcohol acrylate is added, and the mixture is stirred for more than 2 hours to obtain a modified copolymer.
[0165] The same wastewater as in Example 1 was selected, and the scale inhibition test method of Example 1 was used for the scale inhibitor prepared in Comparative Example 6-5. The test found that the scale inhibition rate for calcium ions was 68.3%, and the scale inhibition rate for magnesium ions was 72.1%.
[0166] The present application discloses a method for preparing a modified chitosan scale inhibitor, comprising the steps of: 1, mixing carboxymethyl chitosan and a modified copolymer in a sealed container, then adding a first sulfuric acid solution, stirring, and obtaining a first material; 2, then introducing an inert gas into the first material, and heating the first material to above 100° C. under stirring conditions, then stirring at a constant temperature for a period of time, and then naturally cooling to room temperature to obtain a second material; 3, adjusting the pH of the second material to neutral under stirring conditions, obtaining a precipitate, and sequentially performing The invention discloses a method for preparing a modified chitosan scale inhibitor, wherein the scale inhibitor is washed, dried and ground to obtain a modified chitosan scale inhibitor. The method uses carboxymethyl chitosan, a modified copolymer and a sulfuric acid solution as main raw materials, and controls the mass ratio of the three raw materials. Under the control of the process parameters during the preparation process, the prepared scale inhibitor exhibits excellent scale inhibition and dispersion effects when treating high-salt wastewater. In high-salt wastewater, when the addition amount of the modified chitosan scale inhibitor is 15 mg / L, the scale inhibition rate for calcium ions can reach more than 95%, and the scale inhibition rate for magnesium ions can reach more than 96%, which is convenient for promotion.
[0167] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a modified chitosan scale inhibitor, characterized in that: The following steps are involved: Step 1, mixing carboxymethyl chitosan and modified copolymer in a sealed container, then adding a first sulfuric acid solution, stirring, to obtain a first material; Step 2, then introducing an inert gas into the first material, and heating the first material to above 100° C. under stirring conditions, then stirring at a constant temperature for a period of time, and then naturally cooling to room temperature to obtain a second material; Step 3: Under stirring conditions, adjusting the pH of the second material to neutral, obtaining a precipitate, and sequentially washing, drying and grinding the precipitate to obtain a modified chitosan scale inhibitor; Wherein, the modified copolymer is prepared from the following raw materials by weight: 10 to 20 parts of hydrolyzed polymaleic anhydride; 5 to 10 parts of lauryl alcohol acrylate; 15 to 25 parts of acrylic acid-methyl acrylate-hydroxypropyl acrylate copolymer; 6 to 11 parts of the second sulfuric acid solution; In the step 1, the mass ratio of carboxymethyl chitosan, the modified copolymer and the first sulfuric acid solution is (200-500): (30-70): (30-60); The modified copolymer is prepared by the following method: first, the hydrolyzed polymaleic anhydride and the acrylic acid-methyl acrylate-hydroxypropyl acrylate copolymer are mixed, and then a second sulfuric acid solution is added, and the mixture is stirred for more than 2 hours; then the pH is adjusted to 5-6, and lauryl alcohol acrylate is added, and the mixture is stirred for more than 2 hours to obtain the modified copolymer.
2. The method for preparing the modified chitosan scale inhibitor according to claim 1, characterized in that: In the step 1, the mass ratio of carboxymethyl chitosan to the modified copolymer is 4 to 12:
1.
3. The method for preparing the modified chitosan scale inhibitor according to claim 1, characterized in that: The weight ratio of the total amount of the hydrolyzed polymaleic anhydride and the lauryl alcohol acrylate to the acrylic acid-methyl acrylate-hydroxypropyl acrylate copolymer is 0.8 to 2:
1.
4. The method for preparing the modified chitosan scale inhibitor according to claim 1, characterized in that: In the step 2, the first material is heated to 100° C. to 120° C. and stirred at a constant temperature for more than 6 hours.
5. The method for preparing the modified chitosan scale inhibitor according to claim 1, characterized in that: The carboxymethyl sugar polyshell is prepared from the following raw materials by weight: 50 to 100 parts of alkalized chitosan; 10 to 30 parts of isopropanol; 20 to 60 parts of chloroacetic acid.
6. The method for preparing the modified chitosan scale inhibitor according to claim 5, characterized in that: The carboxymethyl sugar polyshell is prepared by the following method: The alkalized chitosan, the isopropanol and the chloroacetic acid are mixed and stirred for more than 3 hours, and then the pH is adjusted to be neutral, and washed to obtain carboxymethyl chitosan.
7. The scale inhibitor product prepared by the method for preparing the modified chitosan scale inhibitor according to any one of claims 1 to 6.
8. Use of the scale inhibitor product prepared by the method for preparing the modified chitosan scale inhibitor according to any one of claims 1 to 6 in the treatment of high-salt wastewater.